3D-printed nails for aesthetic silicone prostheses. Issue 6 (25th December 2022) - Lee, Felix Austin; Leow, Michael EL; Chiuan YEN, Ching; Wang, Wilson
Abstract : Background and aim: The nail is a crucially important part that needs to be closely reproduced in aesthetic silicone prostheses. The traditional method of producing prosthetic nails is a laborious process often fraught with errors and rejects. In this article, additive manufacturing or 3D printing intervention was sought to make this process less time-consuming and more exacting. Study design and technique: With a focus on finger prosthesis, the process involves reverse engineering a patient's hand using a 3D scanner to obtain a digital blue print for referencing. 3D models of the nail shapes were created using CAD software. Colors sampling is obtained using image processing software from 2D digital images. Using specifically the inkjet technology from Stratasys, batches of nails of different sizes and colors were printed, which were then used for manual adhesion to silicone finger prostheses. Results and conclusions: This article has demonstrated that 3D printing is able to produce nails of comparable quality with those produced by traditional methods in size, shape, curvature, and thickness. More consistent thickness, better size, and shape-matching using 3D files also minimize rejects and grinding time when finishing a prosthesis, leading to significant time savings. However, 3D-printed nails fall short in color match, surface texture, and life-likeness. Traditionally produced nails that are made using a more translucent grade of acrylic than that used in the 3D-printed nails are better able to reproduce the life-like coloration of the translucent human nail. The limitations encountered with 3D printing as applied to prosthetic nails production relate to camera settings, digital image color capture and display, differences in color system used in the printer and monitor, ambient lighting, and suitability of acrylic grade used with the proprietary 3D printing system for material translucency or opacity.